2020
DOI: 10.1111/jace.17034
|View full text |Cite
|
Sign up to set email alerts
|

Design of p‐type NKN‐based piezoelectric ceramics sintered in low oxygen partial pressure by defect engineering

Abstract: The reduction‐resistant properties of piezoelectric ceramics are of great importance for multilayer monolithic structures based on base metal inner electrodes, particularly for recently reported niobate‐based lead‐free perovskites. In this letter, the Hall‐effect measurement and impedance analysis indicate that conventional (K,Na)NbO3 (NKN)‐based ceramics exhibit an n‐type electronic conduction. Rapid increase in the concentrations of oxygen vacancies and electrons is responsible for severe degradation of resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The corresponding equivalent circuits are illustrated in Figure e, and the fitting result is ultimately represented by the red line, which demonstrates excellent accuracy. The activation energy ( E a ) of bulk ceramics ( R b = R g + R gb ) could be calculated by the Arrhenius law as follows , R = R 0 nobreak0em0.1em⁡ exp ( E a K normalB T ) where R 0 is the high-temperature limit of the resistivity, K B is the Boltzmann constant, T is the temperature on the Kelvin scale, and E a is the activity energy of conduction. Plots of ln( R b ) as a function of 1000 T –1 are shown in Figure g, and E a values are derived from the slopes of the fitted lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding equivalent circuits are illustrated in Figure e, and the fitting result is ultimately represented by the red line, which demonstrates excellent accuracy. The activation energy ( E a ) of bulk ceramics ( R b = R g + R gb ) could be calculated by the Arrhenius law as follows , R = R 0 nobreak0em0.1em⁡ exp ( E a K normalB T ) where R 0 is the high-temperature limit of the resistivity, K B is the Boltzmann constant, T is the temperature on the Kelvin scale, and E a is the activity energy of conduction. Plots of ln( R b ) as a function of 1000 T –1 are shown in Figure g, and E a values are derived from the slopes of the fitted lines.…”
Section: Resultsmentioning
confidence: 99%
“…36,37 The electrical responses of ceramic grains and grain boundaries can be observed as two semicircles in different frequency ranges, with the low frequency intercept on the x-axis representing the resistivity of the ceramic at this temperature. 38,39 Figure 3e shows the comparison of impedance spectra of PLCZST ceramics with different contents of Sn 4+ ions at 500 °C. The increase in the Sn 4+ content leads to such a significant rise in the resistivity of the ceramic that the Sn0.5 sample fails to discern any variation in electrical response across the frequency range.…”
Section: Resultsmentioning
confidence: 99%
“…4b only showed a broad peak, indicating one R – C element in the circuit. 38 Thus, a constant phase element (CPE) replaced the standard capacitance C element providing a better fitting result. Here, the CPE is defined by the equation as: 18 where Q is the frequency-independent constant, and ω is the angular frequency.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the KNNbased ceramics have good chemical stability under the reducing condition [14]. Our previous study has verified that the modified KNN-based ceramics could maintain excellent piezoelectric performance in reducing sintering atmosphere by optimizing defect configuration [15][16][17], which demonstrates the feasibility of producing KNN-based MLCA with base Ni/Cu inner electrode. In particular, several studies have indicated that Ni/Cu inner electrodes can be well co-fired with KNNbased ceramics in oxygen-free or oxygen-deficient atmospheres.…”
Section: J U S T a C C E P T E Dmentioning
confidence: 87%